Да. Нет. Не знаю: [роман] / Татьяна Булатова - Булатова Татьяна (Дочки-матери, 2014)
Экземпляры: СБ (201510) / Инвентарный номер: 51437 / Цена: 159.00 / Сис.шифр: Р2 / Авт.знак: Б 90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6